Proceedings of the 2021 Conference of the North American Chapter of the Association for Computational Linguistics: Human Langua 2021
DOI: 10.18653/v1/2021.naacl-main.179
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Framing in Immigration Discourse on Social Media

Abstract: The framing of political issues can influence policy and public opinion. Even though the public plays a key role in creating and spreading frames, little is known about how ordinary people on social media frame political issues. By creating a new dataset of immigrationrelated tweets labeled for multiple framing typologies from political communication theory, we develop supervised models to detect frames. We demonstrate how users' ideology and region impact framing choices, and how a message's framing influence… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(48 citation statements)
references
References 58 publications
1
46
0
1
Order By: Relevance
“…Furthermore, it is grounded heavy in the social science literature. Similar methods could be applied to other major issues such as climate change (Luo et al, 2020a) and immigration (Mendelsohn et al, 2021), where entities include politicians, protesters, and minorities, and where race, mental illness, and unarmed status may all be salient framing devices (e.g. describing the perpetrator or victim of anti-Asian abuse or violence; Gover et al 2020;Chiang 2020;Ziems et al 2020;Vidgen et al 2020).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, it is grounded heavy in the social science literature. Similar methods could be applied to other major issues such as climate change (Luo et al, 2020a) and immigration (Mendelsohn et al, 2021), where entities include politicians, protesters, and minorities, and where race, mental illness, and unarmed status may all be salient framing devices (e.g. describing the perpetrator or victim of anti-Asian abuse or violence; Gover et al 2020;Chiang 2020;Ziems et al 2020;Vidgen et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Field et al (2018) built lexicons from the MFC annotations to classify issue frames in Russian news, and Roy and Goldwasser (2020) extended this work with subframe lexicons to refine the broad categories of the MFC. Some have considered the way Moral Foundations (Haidt and Graham, 2007) can serve as issue frames (Kwak et al, 2020;Mokhberian et al, 2020;Priniski et al, 2021), and others have built issue-specific typologies (Mendelsohn et al, 2021). While issue framing has been well-studied (Ajjour et al, 2019;Baumer et al, 2015), entity framing remains under-examined in NLP with a few exceptions.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous NLP work has shown that agenda setting and framing are two key mechanisms by which attention can be drawn to certain topics (agenda setting) or certain aspects of a topic (framing) during political communication (Card et al, 2015;Tsur et al, 2015;Card et al, 2016;Field et al, 2018;Demszky et al, 2019;Mendelsohn et al, 2021). Here, we use agenda setting and framing to characterize differences between online discussion groups.…”
Section: Related Workmentioning
confidence: 99%
“…Field et al (2018) built lexicons from the MFC annotations to classify issue frames in Russian news, and Roy and Goldwasser (2020) extended this work with subframe lexicons to refine the broad categories of the MFC. Some have considered the way Moral Foundations (Haidt and Graham, 2007) can serve as issue frames (Kwak et al, 2020;Mokhberian et al, 2020;Priniski et al, 2021), and others have built issue-specific typologies (Mendelsohn et al, 2021). While issue framing has been well-studied (Ajjour et al, 2019;Baumer et al, 2015), entity framing remains under-examined in NLP with a few exceptions.…”
Section: Related Workmentioning
confidence: 99%